2019
DOI: 10.1002/cl2.1045
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for climate mitigation in the land use sector—the effects of payment for environmental services on environmental and socioeconomic outcomes in low‐ and middle‐income countries: A mixed‐methods systematic review

Abstract: Unsustainable practices in the land use sector contribute to climate change through the release of greenhouse gases. Payment for environmental services (PESs) provide economic incentives to reduce the negative environmental impacts of land use and are a popular approach to mitigate climate change in low‐ and middle‐income countries. Some PES programmes also aim to improve socioeconomic outcomes and reduce poverty. This systematic review examines the effect of programmes on environmental and socioeconomic outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 98 publications
0
41
0
3
Order By: Relevance
“…While there are no similar reviews of agroforestry interventions, previous reviews have synthesized evidence on the effectiveness of certification schemes and PES programs, which were policy instruments used for several agroforestry interventions included in our review (Oya et al, 2017; Snilstveit et al, 2019). Oya et al (2017) reviewed 43 quantitative and 136 qualitative studies and found that certification schemes tend to increase prices and income from produce but had no consistent effect on wages or household income.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are no similar reviews of agroforestry interventions, previous reviews have synthesized evidence on the effectiveness of certification schemes and PES programs, which were policy instruments used for several agroforestry interventions included in our review (Oya et al, 2017; Snilstveit et al, 2019). Oya et al (2017) reviewed 43 quantitative and 136 qualitative studies and found that certification schemes tend to increase prices and income from produce but had no consistent effect on wages or household income.…”
Section: Discussionmentioning
confidence: 99%
“…They two PES studies we included were also included by Snilstveit et al (2019). They found the PES programs may increase household income and improve environmental outcomes across all PES programs included, which held true when we considered only agroforestry PES programs.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 98%
See 1 more Smart Citation
“…Given a sufficient amount of included qualitative studies, we will conduct a thematic synthesis following the procedures presented in Thomas and Harden (2008) and applied in other Campbell systematic reviews such as that of Snilstveit et al, 2019). A thematic synthesis has three stages, which are interwoven and to an extent overlapping.…”
Section: Methodsmentioning
confidence: 99%
“…However, state ownership is often weakly enforced in practise or is locally contested (Unruh, 2008;Rakotonarivo et al, 2018). While much can be learned from reviews on the importance of various contextual, design, and implementation features on the effectiveness of PES schemes (e.g., Börner et al, 2017;Snilsveit et al, 2019;Wunder et al, 2020), evidence is missing for how the effectiveness of PES in incentivising pro-conservation behaviour might vary between land tenure systems such as communal and individual ownership of forestlands. Yet, pilot or real-world interventions to address this knowledge gap would be difficult to implement because of practical costs and ethical concerns.…”
Section: Introductionmentioning
confidence: 99%